Temporal dynamics of fibrolytic and methanogenic rumen microorganisms during in situ incubation of switchgrass determined by 16S rRNA gene profiling - Piao, Hailan; Lachman, Medora; Malfatti, Stephanie; Sczyrba, Alexander; Knierim, Bernhard; Auer, Manfred; Tringe, Susannah G.; Mackie, Roderick I.; Yeoman, Carl J.; Hess, Matthias (Frontiers in Microbiology, 2014)
The rumen is known for its biomass-degrading and methane-producing phenotype. Fermentation of recalcitrant plant material necessitates the synergistic activity of diverse microbial taxonomic groups that inhabit this anaerobic environment. Although interspecies hydrogen (H2) transfer, a process during which bacterially generated H2 is transferred to methanogenic Archaea, has obtained significant attention over the last decades, the temporal variation of the different taxa involved in in situ biomass-degradation, H2 transfer and methanogenesis process remains to be established. We investigated the temporal succession of microbial taxa and its effect on fiber composition during rumen incubation using 16S rRNA amplicon sequencing. Switchgrass filled nylon bags were placed in the rumen of a cannulated cow and collected at nine time points for DNA extraction and 16S pyrotag profiling. The microbial community colonizing the air-dried and non-incubated switchgrass was dominated by members of the Bacilli. During in situ incubation of the switchgrass, two major shifts in the community composition were observed: Bacilli were replaced within 30 min by members belonging to the Bacteroidia and Clostridia. A second significant shift was observed after 16 h of rumen incubation, when members of the Spirochaetes and Fibrobacteria classes became more abundant in the fiber-adherent community. During the first 30 min of rumen incubation ~13% of the switchgrass dry matter was degraded, whereas little biomass degradation appeared to have occurred between 30 min and 4 h after the switchgrass was placed in the rumen. Interestingly, methanogenic members of the Euryarchaeota increased up to 3-fold during this period of reduced biomass-degradation, with peak abundance just before rates of dry matter degradation increased again. We hypothesize that during this period microbial-mediated fibrolysis was temporarily inhibited until H2 was metabolized into CH4 by methanogens.